PENGARUH PROFITABILITAS, SOLVABILITAS DAN OPINI AUDITOR TERHADAP AUDIT REPORT LAG (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2014 – 2018) - Salwa Febrianti; Sudarno Sudarno (Diponegoro Journal of Accounting, 2020)
This study aims to examine the effect of profitability, solvency and auditor’s opinion on audit report lag on manufacturing companies listed on the Indonesia Stock Exchange in the period 2014 – 2018. The population used in this study is manufacturing companies listed on the Indonesia Stock Exchange in the period 2014 – 2018. The sampling technique used in this study was purposive sampling technique, which is sampling with several criteria. The number of samples that meet the sampling criteria in this study were 47 manufacturing companies (235 sample of data). The results of this study indicate that simultaneously all independent variables namely profitability, solvency and auditor’s opinion affect the audit report lag variable. The partial test results show that the independent variables that influence audit report lag are profitability with significance level of 0,011 and auditor’s opinion with significance level of 0,015. While the solvency variable does not affect the audit report lag because it has a significance level greater than 0,05, namely 0,410.